2021
DOI: 10.1016/j.psj.2020.11.073
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary supplementation of a probiotic (Bacillus subtilis) on bone mass and meat quality of broiler chickens

Abstract: The aim of this study was to investigate the effect of a dietary probiotic supplement on bone mass and meat quality of broiler chickens. Two hundred ten 1-day-old male Ross 708 broiler chicks were divided among 21 floor pens (10 chicks per pen). The pens were randomly distributed to 1 of 3 dietary treatments containing a probiotic, Bacillus subtilis, at 0 (control), 0.25 ( 0.25X ), and 0.5 ( 0.5X ) g/kg (n = 7). Gait score, footpad dermatitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 71 publications
3
21
0
Order By: Relevance
“…Correspondingly, the levels of serotonin were increased in the Raphe nuclei, whereas the concentrations of norepinephrine and dopamine were decreased in the hypothalamus of probiotic-fed broilers. Similar results have been reported in another study, in which probiotic-fed broilers demonstrated a better latency to lie score, an indicator of leg muscle strength, with a greater tibial length, weight, and strength, as well as higher serum calcium and phosphorus concentrations [191]. Increases in the tibia's physical traits (such as thickness of the medial and lateral wall, tibiotarsal index) and bone mineral levels (ash, calcium, phosphorus, bone mineral density, BMD, and bone mineral contents, BMC) were also found in broilers fed with a diet containing B. subtilis and B. licheniformis (BioPlus 28) [198].…”
Section: Bacillus Subtilis and Broiler Skeletal Health In Broilerssupporting
confidence: 89%
“…Correspondingly, the levels of serotonin were increased in the Raphe nuclei, whereas the concentrations of norepinephrine and dopamine were decreased in the hypothalamus of probiotic-fed broilers. Similar results have been reported in another study, in which probiotic-fed broilers demonstrated a better latency to lie score, an indicator of leg muscle strength, with a greater tibial length, weight, and strength, as well as higher serum calcium and phosphorus concentrations [191]. Increases in the tibia's physical traits (such as thickness of the medial and lateral wall, tibiotarsal index) and bone mineral levels (ash, calcium, phosphorus, bone mineral density, BMD, and bone mineral contents, BMC) were also found in broilers fed with a diet containing B. subtilis and B. licheniformis (BioPlus 28) [198].…”
Section: Bacillus Subtilis and Broiler Skeletal Health In Broilerssupporting
confidence: 89%
“…The poultry meat quality can generally be evaluated by pH value, water holding capacity and shear force ( 61 ). Various aspects influence muscle pH value changes, and the direct influence factor is muscle glycolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Various aspects influence muscle pH value changes, and the direct influence factor is muscle glycolysis. The pH value visualizes muscle acidity and alkalinity and can directly impact muscle tenderness and drip loss ( 61 ). In this study, the BMpH in HLG100 and HLG200 was lower, the LMpH in the treated groups with hydroxylated lecithin and soy lecithin was lower, indicating that hydroxylated lecithin could reduce the pre-growth muscles pH value of geese.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, hens supplemented with additives performed standing behavior more frequently and for a longer time, which could indicate greater exercise and is beneficial for leg muscles and bones, especially in caged birds ( 42 ). Mohammed et al ( 43 ) observed that broilers supplemented with probiotics spent more time standing in the latency-to-lie test. They also observed higher tibial physical parameters (length, weight, and strength), in addition to higher concentrations of calcium and phosphorus in the blood.…”
Section: Discussionmentioning
confidence: 99%